Equal pay for work of equal value, wage-setting and the gender pay gap. (September 2020) - Whitehouse, Gillian; Smith, Meg
The principle of equal pay for work of equal value has radical potential but uneven application and impact. As one strand within the multiplicity of measures required to impede the reproduction of gender pay gaps, its strengths lie in an expanded notion of equality and capacity to challenge gendered norms embedded in wage-setting practices. Almost 70 years after the principle was given expression in the International Labour Organisation's Equal Remuneration Convention of 1951, these strengths remain difficult to capture. This collection includes studies of advances and retreats in Australia and New Zealand, shaped by political and economic trends, changing wage-setting arrangements and varying interpretations of formal provisions. These are elaborated with examples of collective action that have redefined the problem of gender pay inequality and found pathways to redress gender-based undervaluation in the absence of a supportive regulatory framework. Studies of three East Asian countries extend understanding through stark illustrations of recurring barriers, highlighting limitations in legal expression, incompatibility of equal value measures with wage-setting norms, and the impact of highly segmented labour markets. Together the articles underline the need for interrelated reforms to formal provisions, wage-setting institutions and labour markets, and the importance of ongoing mobilisation to drive change.